TORT AS A BASIS FOR CANCELLATION OF A LAND SALE AND PURCHASE AGREEMENT - Pamungkas, Christ Prihantoro; Santosa, Budi (Jurnal Meta-Yuridis, 2025)
This study aims to investigate the legal provisions regarding the cancellation of land purchase agreements and the legal implications of unilateral cancellation. The research method used is normative legal research with a literature approach, using 3 types of legal materials: primary, secondary, and tertiary. This study focuses on literature review to analyze the applicable legal rules. The results show that the cancellation of land purchase agreements can be a solution to resolve disputes related to transactions with legal defects. This can be due to either not meeting the legal requirements for the agreement or due to unlawful acts. Based on Article 1338 paragraph (1) of the Indonesian Civil Code, society can make binding agreements, including land purchase agreements. The consequences of unilateral cancellation of land purchase agreements are: 1. Termination of the agreement and refund of the money paid by the buyer to the seller after deducting a percentage from the selling price and imposing a fine. 2. The parties may be subject to fines according to the mutual agreement, which must be paid for each day of delay. The responsibility for the actions of each party is an obligation that must be fulfilled